2022
DOI: 10.14814/phy2.15479
|View full text |Cite
|
Sign up to set email alerts
|

Does plantar skin abrasion affect cutaneous mechanosensation?

Abstract: In humans, plantar cutaneous mechanoreceptors provide critical input signals for postural control during walking and running. Because these receptors are located within the dermis, the mechanical properties of the overlying epidermis likely affect the transmission of external stimuli. Epidermal layers are highly adaptable and can form hard and thick protective calluses, but their effects on plantar sensitivity are currently disputed. Some research has shown no effect of epidermal properties on sensitivity to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…By analysing the VPT and using the SWMT, we can assess the dorsal column-medial lemniscal system and identify large fibre neuropathy. 19,55,56 Prior to the assessment of each sensation, the patients were reminded that when they perceived the stimulus, they had to express this verbally. They were reminded of this procedure as many times as necessary during the examination, and we avoided asking if they noticed it every time we stimulated an area, as this could pressure the patients to answer 'yes' and misrepresent the results of the investigation.…”
Section: Peak Accelerationmentioning
confidence: 99%
See 3 more Smart Citations
“…By analysing the VPT and using the SWMT, we can assess the dorsal column-medial lemniscal system and identify large fibre neuropathy. 19,55,56 Prior to the assessment of each sensation, the patients were reminded that when they perceived the stimulus, they had to express this verbally. They were reminded of this procedure as many times as necessary during the examination, and we avoided asking if they noticed it every time we stimulated an area, as this could pressure the patients to answer 'yes' and misrepresent the results of the investigation.…”
Section: Peak Accelerationmentioning
confidence: 99%
“…6 (7.1%) of the participants had no treatment for diabetes. 19 A sensory neuropathy evaluation was conducted using different tools on the feet to that end (Table 3).…”
Section: Description Of the Samplementioning
confidence: 99%
See 2 more Smart Citations
“…The same is true for all the suprabasal layers of the volar epidermis, such that according to one study the plantar epidermis is about 6-fold thicker than the epidermis on the dorsal foot ( 13 ). The greatly thickened volar epidermis may be expected to interfere with sensory function since mechanoreceptors in the skin are all located in the dermis, but it has been shown that foot callus thickness does not negatively affect sensitivity toward the types of tactile stimuli typically encountered during standing and walking ( 19 , 20 ). This implies that volar skin must be stiff enough to transmit mechanical forces from the skin surface to the dermal mechanoreceptors with negligible dampening.…”
Section: Atypical Structural and Mechanical Propertiesmentioning
confidence: 99%